Evaluation of the possibilities for stream restoration: preassessment of the Váli-stream (Hungary) - Zsombor Boromisza; Zsuzsanna Illyés; Attila Gergely; Szilvia Mészáros; Zsófia Monspart-Molnár (Acta Geographica Debrecina. Landscape & Environment Series)
The purpose of this study is to evaluate the potential of restoration of a stream section. The starting point of the multiple-step assessment process was a historical analysis, which resulted in the definition of different sections within the study area, providing a base for the further restoration goals. The assessment of the current conditions was elaborated particularly to determine those factors, which could limit restoration. These assessments cover the land use pattern, furthermore the analysis of vegetation and habitat patches. As a result of the historical analysis, it has been found that the stream side habitat patches have decreased significantly despite the constant space available. This change was not caused by the increased area of the settlement, but rather by the higher dominancy of arable forms of land use. The greatest share of wet and mesic meadows and agricultural habitats in the study areas, covering 57.5% of the total area, indicates significant anthropogenic effects. Consequently it can be stated that the reference conditions are not the only determining factors of the restoration possibilities. Restoration style and intensity have been defined on basis of all assessed factors.